FECUNDITY FLUCTUATIONS IN THE OIL-SARDINE, SARDINELIA LONGICEPS VAL. - Raja, B T Antony (Indian Journal of Fisheries, 2011)
The functional relationship between fecundity and length in the oil-sardine is curvilinear and that between fecundity and weight is rectilinear. Comparing the relative merits of the two relationships, the study has revealed that it cannot be held that the fecundity,-weight relationship is better as a rule. On the other hand, a comparison made of expected fecundity and weight ad’usted to a common length shows that, in general, the heavier fish of identical length are more fecund. For a given length or weight the fecundity variations are considerable.